Informal consultations and the work routine of Brazilian pediatricians before and during the COVID-19 pandemic. - Pasa Morgan, M.A.; Lopes Fatturi, A.; Oliveira de Carvalho, V. (European Journal of Pediatric Dermatology, 2022)
Objectives. “Quick peeks” or “curbside consultations” are informal consultations (IC) that consist of giving an informal opinion on a question from a physician or a patient. With the need for social isolation determined by the COVID-19 pandemic, maybe the IC have been used even more. The present study assessed the impact of IC on pediatrician routine in the COVID-19 pandemic. Methods. This was an observational, analytical, and cross-sectional study with prospective data collection. Pediatricians who received an e-mail invitation to participate in the online survey were included. Results. 852 pediatricians answered the questionnaire, and 93.2% (810) conducted IC during 2020 and 2021. There was a 50% to 90% increase in the number of IC. The main reasons given for conducting an IC were to help patients (60.1%) and because they also asked colleagues for their opinion (71%). Almost all the IC (99%) were conducted without remuneration and 61.8% of the participants indicated that they would like compensation to be formalized. Conclusions. IC became more frequent in the pediatric area during the COVID-19 pandemic, but they represent an overload of work and are not remunerated. A standardization of the service provided is needed.